Serological Evidence of Increased Coccidioides immitis Infections in Western Canada in 1996 - Errol Prasad; Patricia Diediw; Donna Fernandes; Lorreen Hodge; Katherine Ower; Robert Rennie (Canadian Journal of Infectious Diseases)
OBJECTIVE: To investigate the epidemiology of Coccidioides immitis infection in persons returning to western Canada from C immitis endemic zones in southwestern United States.